2022
DOI: 10.3390/w14111764
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Standardized Precipitation Evapotranspiration Index Using Data-Driven Techniques: A Regional Study of Bangladesh

Abstract: Drought prediction is the most effective way to mitigate drought impacts. The current study examined the ability of three renowned machine learning models, namely additive regression (AR), random subspace (RSS), and M5P tree, and their hybridized versions (AR-RSS, AR-M5P, RSS-M5P, and AR-RSS-M5P) in predicting the standardized precipitation evapotranspiration index (SPEI) in multiple time scales. The SPEIs were calculated using monthly rainfall and temperature data over 39 years (1980–2018). The best subset re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 72 publications
2
5
0
Order By: Relevance
“…The weighted scores based on multiple evaluation metrics provide a comprehensive assessment of the model's predictive capabilities. M5P models also did a remarkable performance in estimating ETo same work was done by Elbeltagi et al, (Elbeltagi et al, 2022) with the M5P tree and their hybridized versions (AR-RSS, AR-M5P, RSSM5P, and AR-RSS-M5P). The evaluation of the GEP model showed slightly lower performance in terms of NSE and MAE compared to the ANFIS and M5P models.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The weighted scores based on multiple evaluation metrics provide a comprehensive assessment of the model's predictive capabilities. M5P models also did a remarkable performance in estimating ETo same work was done by Elbeltagi et al, (Elbeltagi et al, 2022) with the M5P tree and their hybridized versions (AR-RSS, AR-M5P, RSSM5P, and AR-RSS-M5P). The evaluation of the GEP model showed slightly lower performance in terms of NSE and MAE compared to the ANFIS and M5P models.…”
Section: Discussionsupporting
confidence: 62%
“…In recent years, data-driven models, including stochastic and arti cial intelligence methods, have demonstrated their e cacy in modeling and predicting hydrometeorological variables, presenting e cient approaches for ETo modeling and forecasting. These models have shown promising performance and offer a valuable tool set for studying and predicting ETo variations in different spatiotemporal scales (Dehghanisanij et al, 2022) (Elbeltagi et al, 2022) (Azad et al, 2022). Accurate prediction of evapotranspiration holds immense signi cance, particularly in regions like Iran that face limited water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Although we selected the 3 and 12 month timescales, several research studies, such as [34,136,137], have reported the feasibility of considering other timescales. Drought and wetness analyses can be performed on a variety of timescales, depending on the need.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity and non-linearity of the drought process, simulations using non-linear time series data are necessary. Consequently, machine learning (ML) systems for drought forecasting have attracted considerable interest [14,15]. In addition, several types of research have shown that AI algorithms outperform conventional approaches [16][17][18][19], such as artificial neural network (ANN) [20], support vector machines (SVMs) [21], random forests [22], and the adaptive neuro-fuzzy inference system (ANFIS) [23], which are examples of these ML systems.…”
Section: Introductionmentioning
confidence: 99%